Move and Agree in Arabic Construct State: A Phase-based Analysis - Alenazy, Mamdouh (Jordan Journal of Modern Languages & Literatures, 2025)
This paper investigates the internal structure of Arabic Construct State in light of the latest advances within the Minimalist Program. It adopts a phase-based Agree model to account for how word order and Case value are determined within the structure of the Construct State which is represented as a DP phase within which the head noun undergoes N to D movement. The derivation of the Construct State structure does not involve any unnecessary PF linearization process to ensure that the surface word order is achieved. Instead, the paper shows that the surface word order is the outcome of movement of the head noun to D, the head DP phase. Since the head noun is the head of the lexical core and locus of φ-features, it receives Case under Agree with an external probe; the Case value it receives is spread within NP and copied on the modifying attributive adjectives. Keywords: Phase Theory, Agree Theory, Minimalism, Arabic, Construct State, DP. Highlights: Arabic Construct State is composed of a head noun and an associate DP Arabic Construct State is a possessive construction that lacks an overt possessive marker. The analysis provided adopts Phase theory to account for how word order Case values in Arabic Construct State are determined Arabic Construct State is analyzed as a DP phase which has an inaccessible domain The internal structure of Arabic Construct State is built by movement of the head noun to D, the head of the Construct State